Editorial: Adipose tissue and skeletal muscle as endocrine organs: Role of cytokines in health and disease - Duarte, Ana Claudia Garcia De Oliveira (2022)
Department of Physical Education and Human Motricity-DEFMH Biological and Health Sciences Center- CCBS Federal University of São Carlos-UFSCar